The Role of Compensation to Work Satisfaction and Employee Performance of Steel Fabricator Companies in East Java - A, Sundjoto (International Journal of Scientific Research and Management (IJSRM), 2017)
This study explains the relationship between compensation to job satisfaction and employee performance of steel fabricator company in East Java. Data were obtained in this study from a sample of 170 employees of the operator level in the production department consisting of fitter, welder and helper. The results obtained in this study there are three findings. First, compensation has significant effect on job satisfaction with p value 0,004. Second, the compensation significantly affects employee performance with the p value of 0,043 and the third job satisfaction significantly influence the performance with the result p value of 0,036. This study also shows that the compensation variable is not dominant to form the performance but must pass the employee's job satisfaction first.